Sexual behavior in adolescents: concepts, practices, and expectations - Coronado, Jhon; Moreno, Duván (Revista Acciones Médicas, 2025)
Sexual behavior during adolescence constitutes a complex phenomenon influenced by sociocultural and educational factors that shape the ways in which young people understand and practice their sexuality. Objective: To analyze the concepts, practices, and expectations surrounding the sexual behavior of adolescents in the municipality of Ramiriquí, Boyacá, Colombia. Method: A qualitative approach was employed, supported by a narrative topical design. Data were collected through semi-structured interviews conducted with 40 students (20 females and 20 males) aged between 15 and 17 years, selected through non-probabilistic convenience sampling. Data analysis was performed using axial coding. Results: The main findings reveal that adolescents hold distorted ideas and notions regarding anatomy, corporeality, sexual relationships, the duration and expectations of sexual activity, orgasm, sexual and physical attractiveness, as well as aspects related to communication, emotional intimacy, and education. These misconceptions lead to insecurities, emotional distress, and risk-taking practices that deviate from healthy sexuality. Conclusions: This situation appears to be shaped by the lack of clear and accurate information on the subject, the influence of pornography, exposure to explicit content in mass media and social networks, the prevalence of sociocultural stereotypes, and peer pressure.
Keywords: anatomy; adolescents; behavior; sex; sexuality